Myths in scientific publishing of law journals: the brazilian experience (De Legibus - Law Journal, 2025)
After a brief look at the role of a scientific journal, this paper offers a review of the literature on scientific publishing in order to analyze six rarely debated issues regarding the submission guidelines of Brazilian law journals: 1) the use of the Qualis/CAPES concept to evaluate journals; 2) the requirement of a doctoral degree from the authors of submissions, 3) the possibility of only one doctor evaluating the work of another doctor; 4) the importance of special issues; 5) the prohibition on an editor publishing in his own journal and 6) the practice of publishing legal opinions in law journals. After the analysis, it was concluded that i) the use of the Qualis/CAPES concept as an indicator of journal quality was incorrect; ii) academic titles should not be required of authors who submit works; iii) peer review should prioritize knowledge rather than academic titles; iv) without the adoption of good parameters, special issues can lead to bad editorial practices and scientific misconduct; v) under certain conditions, it is possible for an editor to publish in his own journal and vi) given the high probability of a conflict of interest, the publication of legal opinions in law journals should be prohibited.
Keywords: scientific publishing; law review; law journal; perverse incentives; legal opinions